2007
DOI: 10.1515/znc-2007-3-404
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Extract, Fractions and Four Compounds Extracted from Piper solmsianum C. DC. var. solmsianum (Piperaceae)

Abstract: Piper solmsianum C. DC. var. solmsianum (Piperaceae) is a shrub commonly found in areas with wet tropical soils. Other Piper species have been used in folk medicine as antitumoral and antiseptic agents. We studied the crude methanolic extract, some organic fractions and compounds isolated from this plant for possible antimicrobial activity against Grampositive and Gram-negative bacteria. The bioautographic assays disclosed three inhibition zones. The minimal inhibitory concentration (MIC) and minimal bacterici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 29 publications
1
10
0
4
Order By: Relevance
“…Phytochemical studies revealed the presence of monoterpenes, sesquiterpenes, arylpropanoids, phenylpropanoids, lignans and neolignans, most of which showing biological activity against bacteria, fungus and the trypomastigote form of Trypanossoma cruzi (Moreira et al 1995;Martins et al 2000;Campos et al 2005;2007).…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemical studies revealed the presence of monoterpenes, sesquiterpenes, arylpropanoids, phenylpropanoids, lignans and neolignans, most of which showing biological activity against bacteria, fungus and the trypomastigote form of Trypanossoma cruzi (Moreira et al 1995;Martins et al 2000;Campos et al 2005;2007).…”
Section: Introductionmentioning
confidence: 99%
“…We have conducted some studies with this plant (leaves) at our laboratories, and confirmed that fractions and some pure compounds (lignans) exhibit pronounced antibacterial and antifungal properties [13,14].…”
Section: Introductionmentioning
confidence: 65%
“…Hexane (3.3 g) and ethyl acetate (6.6 g) fractions were fractionated on silica gel column chromatography and eluted as previously described [14] to give pure conocarpan (686 mg) and orientin (765 mg), respectively, together with other compounds not studied here. The identification of the isolated compounds was performed by direct comparison with authentic samples previously described for this plant and spectral data [14].…”
Section: Preparation Of Extract Fractions and Isolation Of Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…The minimum inhibitory concentration (MIC) was determined by the agar dilution method, according to reported procedures (Campos et al, 2007), which was carried out on slants (1 mL). Stock solutions of ethyl acetate III (EAIII) in dimethylsulfoxide (DMSO) was diluted to give serial two-fold dilutions, which were added to medium (MHA), resulting in concentrations ranging from 0.010 to 10 mg/mL.…”
Section: Quantitative Antimicrobial Evaluation In Vitromentioning
confidence: 99%